Fast crystal growth at ultra-low temperatures - Gao, Qiong; Ai, Jingdong; Tang, Shixiang; Li, Minhuan; Chen, Yanshuang; Huang, Jiping; Tong, Hua; Xu, Lei; Xu, Limei; Tanaka, Hajime; Tan, Peng (Nature materials, 2021)
It is believed that the slow liquid diffusion and geometric frustration brought by a rapid, deep quench inhibit fast crystallization and promote vitrification. Here we report fast crystal growth in charged colloidal systems under deep supercooling, where liquid diffusion is extremely low. By combining experiments and simulations, we show that this process occurs via wall-induced barrierless ordering consisting of two coupled steps: the step-like advancement of the rough interface that disintegrates frustration, followed by defect repairing inside the newly formed solid phase. The former is a diffusionless collective process, whereas the latter controls crystal quality. We further show that the intrinsic mechanical instability of a disordered glassy state subject to the crystal growth front allows for domino-like fast crystal growth even at ultra-low temperatures. These findings contribute to a deeper understanding of fast crystal growth and may be useful for applications related to vitrification prevention and crystal-quality control. Charged colloidal systems undergo fast crystallization under deep supercooling due to a coupled mechanism involving the discrete advancement of the crystal growth front and defect repair inside the recently formed solid phase.